In-Vitro Bond Strength of a Flowable Compomer to Primary Teeth Dentin with Different Applying Techniques - Levent Özer; Ece Öztoprak; Elif Şenay; Bahar Zincir (Ankara University, 2022)
Purpose: The study aimed to investigate the effect of applying flowable compomer using different techniques and long-term water storage on microtensile bond strength (µTBS) to primary teeth dentin and present a comparison with packable compomer. Materials and methods: 90 primary molars were used to evaluate the µTBS of the materials. Specimens were randomly divided into 3 main groups for restoration: Group 1 and 4, compomer (Glasiosite, VOCO GmbH, Cuxhaven, Germany) filling alone; Group 2 and 5, flowable compomer (Twinky Star Flow, VOCO GmbH, Cuxhaven, Germany) lining/pre-cured and overlaying compomer; and Group 3 and 6, flowable compomer lining/co-cured with overlaying compomer. All specimens were thermocycled (500X), after which half of them (n=45) were stored in distilled water for 24 h (Group A: Groups 1-3), and the remaining half (n=45) for 24 months (Group B: Groups 4-6). Samples were tested for µTBS (1 mm/min) with a microtensile testing machine (T 61010 Ki, Bisco, Schaumburg, USA). Failure modes were determined with the aid of a stereomicroscope. Results were analyzed using the Kruskal-Wallis H test. Results: There was no statistically significant difference between the groups regarding bond strength (p gt;0.05). Mixed cohesive failure of both adhesive and dentin was the most common type of failure in all groups (p lt;0.05). 2-year water storage significantly decreased the bond strength for all groups (p lt;0.05). Conclusion: Flowable compomers applied using different techniques produced similar bond strength to dentin compared to compomer. However, long-term water storage decreased bond strength significantly.